If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(9x + -1) + 9 = 9(7x + 9) Reorder the terms: 7(-1 + 9x) + 9 = 9(7x + 9) (-1 * 7 + 9x * 7) + 9 = 9(7x + 9) (-7 + 63x) + 9 = 9(7x + 9) Reorder the terms: -7 + 9 + 63x = 9(7x + 9) Combine like terms: -7 + 9 = 2 2 + 63x = 9(7x + 9) Reorder the terms: 2 + 63x = 9(9 + 7x) 2 + 63x = (9 * 9 + 7x * 9) 2 + 63x = (81 + 63x) Add '-63x' to each side of the equation. 2 + 63x + -63x = 81 + 63x + -63x Combine like terms: 63x + -63x = 0 2 + 0 = 81 + 63x + -63x 2 = 81 + 63x + -63x Combine like terms: 63x + -63x = 0 2 = 81 + 0 2 = 81 Solving 2 = 81 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 25s^2+80s=-64 | | x-3.5=7 | | 7(9n-1)+9=9(7n+9) | | 9+16m-6=9m+45-7m | | 3+x-2(-4)=7-(-13) | | 100r^2-9=0 | | n-6=-15 | | 8-2(a+1)=9+a | | -3(5y+1)=5(1-3y)-8 | | c=tp | | b^2+12b+32=0 | | -56=8-2w | | 3x+40=2x+50 | | 1.6q-2.4-2.1q=-1.5q-3.5 | | -13m+8m=17-57 | | 120=(2x+1)(x+1) | | 91=(x+1)(x+2) | | X-5(4)+7=35 | | 3x+8x-7=21x-5 | | 2x-5=37 | | -18x=234 | | 9m^2-3m-2=0 | | -3q=54 | | 3a^2+8a-3=0 | | 133=(2x+1)(x+1) | | 6w=72 | | 2x^3+8x^2+6x=0 | | 2y+6y=56 | | -6(3b+2)+(19b-9-9)=0 | | 6t=-45 | | t+34-25t=4 | | 9t=-18 |